Novel cassane diterpenes from the seeds of Caesalpinia decapetala and their antiproliferative activity. (June 2016) - Ma, Guo-Xu; Chen, Ping; Sun, Zhong-Hao; Zhu, Nai-Liang; Li, Peng-Fei; Yang, Jun-Shan; Chen, De-Li; Wei, Hua
Graphical abstract: Highlights: Two new cassane diterpenes were isolated from the seeds of Caesalpinia decapetala . Compounds 2 represents a new diterpene with the cleavage of C-13/14 bond. Compound 1 had selectively cytotoxic activity, with IC50 value of 9.6 μM. Abstract: Two new cassane diterpenes, caesaldecapes A-B (1 –2 ), were isolated from the seeds of Caesalpinia decapetala . Their structures were elucidated by extensive spectroscopic methods, including NMR, MS, and HRESIMS. Compounds1 –2 are novel examples of rearranged cassane diterpenes obtained from C. decapetala . The two compounds were evaluated for their antiproliferative activity in vitro against four human cancer cell lines, and compound1 showed selectively cytotoxic activity against KB cancer cell lines, with an IC50 value at 9.6 μM.